Krisis Identitas Profesi Konselor di Indonesia - Pratama, Ari Yoga; Hidayah, Nur (JURNAL KONSELING GUSJIGANG, 2019)
The writing purpose of this article is to recover the identity of counselor’s profession. The counselor's profession has a significant development from 1900 to the present. But there is a problem in counselor’s profession. This is about crisis of identity. The counselor's professional identity crisis arises because of four counselor problem myths. In Indonesia the counselor profession is still not widely known by the community. This is because there are still many negative perceptions that arise in Indonesia. The counselor's identity can be seen from how a counselor can fulfill the requirements which includes has taken a Bachelor's Degree and get passed,  has an knowledge of his professional identity, has the basic nature of the counselor and has a knowledge which covers theory and practice and also can carry out the assignment in school. Through these requirements, the counselor’s profession identity will be formed and will be more stronger.